2018
DOI: 10.3390/ma11122596
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and Shear Strain Characteristics of Carbon Fiber Reinforced Polymer Composite Adhered to a Concrete Surface

Abstract: The use of Fiber Reinforced Polymer (FRP) composites for strengthening concrete structures has gained a lot of popularity in the past couple of decades. The major issue in the retrofitting of concrete structures with FRP is the accurate evaluation of flexural and shear strains of polymer composites at the bonding interface of epoxy and concrete. To address it, a comprehensive experimental study was planned and carbon fiber reinforced polymer (CFRP) composite was applied on the concrete surface with the help of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Concrete is a widely used construction material in building infrastructure all around the world owing to its ability to be cast into shape, durability, cost-effectiveness, and high compressive strength [ 1 , 2 , 3 ]. Poor quality control during the construction process; the corrosion of steel reinforcement; design errors; natural disasters such as earthquakes, explosions, and hurricanes; and harsh environments are some major factors that degrade the durability and strength of reinforced concrete (RC) structures during their design life [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ]. Demolishing and rebuilding or adding extra structural members to enhance the strength of a concrete structure is often regarded as an uneconomical and unsustainable strategy and thus requires huge investments [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concrete is a widely used construction material in building infrastructure all around the world owing to its ability to be cast into shape, durability, cost-effectiveness, and high compressive strength [ 1 , 2 , 3 ]. Poor quality control during the construction process; the corrosion of steel reinforcement; design errors; natural disasters such as earthquakes, explosions, and hurricanes; and harsh environments are some major factors that degrade the durability and strength of reinforced concrete (RC) structures during their design life [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ]. Demolishing and rebuilding or adding extra structural members to enhance the strength of a concrete structure is often regarded as an uneconomical and unsustainable strategy and thus requires huge investments [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, carbon-fiber-reinforced polymer (CFRP) plates and sheets are widely used in the construction industry for the strengthening and retrofitting of reinforced beams in flexure and shear [ 4 , 8 , 13 , 14 , 15 ]. CFRP possesses a high strength-to-weight ratio, flexibility, resistance to corrosion, good ductility, and ease of installation [ 8 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, strengthening with FRP composites significantly contributed to improving the flexural and shear capacity and increasing the fatigue life of structural members [ 10 ]. Practically until now, efforts are being made to avoid premature peeling off products made of this outstanding but also expensive material [ 11 ], e.g., externally bonded reinforcement on grooves (EBROG) and externally bonded reinforcement in grooves (EBRIG) bonding technique [ 12 , 13 ] or mechanical anchorage application [ 14 ]—these solutions allowed for some improvement in the efficiency of externally bonded FRPs.…”
Section: Introductionmentioning
confidence: 99%
“…Externally bonded fiber reinforced polymer (FRP) is widely used as a proven reinforcement technique for masonry structures [ 1 , 2 , 3 , 4 , 5 ]. Practical applications and numerous studies have found that the debonding of FRP from the surface of substrates (e.g., concrete, clay brick and mortar) is the principal failure mode of reinforced structures [ 1 , 6 , 7 , 8 , 9 ]. The bond–slip relationship between FRP and substrate is the basis for understanding the process of interfacial debonding.…”
Section: Introductionmentioning
confidence: 99%